Augmented latissimus dorsi transfer: initial results in patients with massive irreparable posterosuperior rotator cuff tears. (May 2019) - Sidler-Maier, Claudia C.; Mutch, Jennifer A.; Sidler, Martin; Leivadiotou, Dimitra; Payandeh, Jubin B.; Nam, Diane
Background: The surgical treatment of irreparable massive rotator cuff tears is challenging. The purpose of the present study was to report the initial outcomes after a modified latissimus dorsi transfer (LDT) augmented by acellular dermal allograft (ADA). Methods: This retrospective study includes 24 patients managed with LDT using ADA augmentation as a bursal-sided onlay between March 2009 and December 2015. Results: All patients were men with a mean age of 57 years (range 48 years to 70 years). Seven patients had a previously failed rotator cuff repair and ten patients presented with a deficient subscapularis tendon. At last follow-up (mean 27 months), there was a significant improvement in active forward flexion (mean increase 31°; p = 0.016), and abduction by 25° ( p = 0.059). The acromiohumeral distance remained stable and the failure rate was low (4%). Neither a history of previous rotator cuff surgery, nor the presence of a subscapularis tear had a negative impact on functional outcome. Conclusions: In our cohort of patients, LDT augmented with ADA was a reasonable option for patients with previously failed rotator cuff repair, as well as in the subgroup of patients with a deficient subscapularis tendon. Level of evidence: Level IV: Therapeutic study (case series)